2015
DOI: 10.1097/md.0000000000000842
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Systolic Blood Pressure Within the Normal Range Are Associated With Significantly Elevated Risks of Nonalcoholic Fatty Liver Disease

Abstract: A positive association between hypertension or high-normal blood pressure (BP) and risk of nonalcoholic fatty liver disease (NAFLD) is well-known; however, no data have been generated exploring the risk of NAFLD within the normal range of BP. We aimed to assess the association between normal systolic blood pressure (SBP) and risk of NAFLD.A total of 27,769 subjects from 2 separate medical centers were included. Subjects were divided into 4 groups (G1 to G4) by SBP levels: G1: 90–99 mmHg, G2: 100–109 mmHg, G3: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 38 publications
(41 reference statements)
4
28
1
1
Order By: Relevance
“…In addition, our findings suggest that the NAFLD combined with type 2 diabetes group had the highest level of diastolic blood pressure. The results of Shengjie Wu et al . suggest that increased levels of systolic blood pressure within the normal range are associated with significantly elevated risk for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our findings suggest that the NAFLD combined with type 2 diabetes group had the highest level of diastolic blood pressure. The results of Shengjie Wu et al . suggest that increased levels of systolic blood pressure within the normal range are associated with significantly elevated risk for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our findings suggest that the NAFLD combined with type 2 diabetes group had the highest level of diastolic blood pressure. The results of Shengjie Wu et al 27 suggest that increased levels of systolic blood pressure within the normal range are associated with significantly elevated risk for NAFLD. Aneni et al 28 reported that controlling blood pressure among non-obese hypertensive patients might be beneficial in preventing or limiting NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Fasting venous blood sample collection (required an overnight fast) would be measured with an automated analyzer (Abbott AxSYM). More specific details were presented in the previous reports [8,11].…”
Section: Data Collectionmentioning
confidence: 99%
“…Blood pressure (BP), including systolic blood pressure (SBP) and diastolic blood pressure (DBP), is an important risk factor for developing NAFLD [7][8][9][10], even in individuals without hypertension [10]. Mean arterial pressure (MAP), a steady component of BP, has wildly been used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation